Pengaruh Motivasi dan Komitmen Organisasi Terhadap Kinerja Pegawai Dengan Kepuasan Kerja Sebagai Variabel Mediasi Pada Badan Penghubung Daerah Provinsi Jawa Timur - Wakhid Sutarto; Guswandi; Tatag Herbayu (Jurnal Manajemen Bisnis Krisnadwipayana, 2025)
This study aims to analyze the influence of motivation and organizational commitment on employee performance, with job satisfaction as a mediating variable at the Regional Liaison Agency of East Java Province. This study uses a quantitative approach with a survey method. The population in this study were all employees of the Regional Liaison Agency of East Java Province. The data analysis technique used path analysis to test the direct and indirect effects between variables. The results show that motivation and organizational commitment have a positive and significant effect on job satisfaction and employee performance. In addition, job satisfaction also has a significant effect on employee performance and is able to partially mediate the relationship between motivation and organizational commitment on employee performance.